(untitled) (Conferencea, 2023)
Stroke is the second most common cause of death and the leading cause of disability in adults worldwide. Acute cerebral infarction is caused by a sharp decrease in blood and oxygen supply. Treatment strategies currently available time in Western countries for occlusion of large vessels include the rapid restoration of blood flow by removing the problematic blood clot using mechanical or pharmacological means (for example, tissue plasma activator).